Global characteristics and outcomes of SARS-CoV-2 infection in children and adolescents with cancer (GRCCC): a cohort study. Issue 10 (October 2021) - Mukkada, Sheena; Bhakta, Nickhill; Chantada, Guillermo L; Chen, Yichen; Vedaraju, Yuvanesh; Faughnan, Lane; Homsi, Maysam R; Muniz-Talavera, Hilmarie; Ranadive, Radhikesh; Metzger, Monika; Friedrich, Paola; Agulnik, Asya; et al.
Summary: Background: Previous studies have shown that children and adolescents with COVID-19 generally have mild disease. Children and adolescents with cancer, however, can have severe disease when infected with respiratory viruses. In this study, we aimed to understand the clinical course and outcomes of SARS-CoV-2 infection in children and adolescents with cancer. Methods: We did a cohort study with data from 131 institutions in 45 countries. We created the Global Registry of COVID-19 in Childhood Cancer to capture de-identified data pertaining to laboratory-confirmed SARS-CoV-2 infections in children and adolescents (<19 years) with cancer or having received a haematopoietic stem-cell transplantation. There were no centre-specific exclusion criteria. The registry was disseminated through professional networks through email and conferences and health-care providers were invited to submit all qualifying cases. Data for demographics, oncological diagnosis, clinical course, and cancer therapy details were collected. Primary outcomes were disease severity and modification to cancer-directed therapy. The registry remains open to data collection. Findings: Of 1520 submitted episodes, 1500 patients were included in the study between April 15, 2020, and Feb 1, 2021. 1319 patients had complete 30-day follow-up. 259 (19·9%) of 1301 patients had a severe or critical infection, and 50 (3·8%) of 1319 died with the cause attributed to COVID-19 infection. Modifications to cancer-directed therapy occurred in 609 (55·8%) of 1092 patients receiving active oncological treatment. Multivariable analysis revealed several factors associated with severe or critical illness, including World Bank low-income or lower-middle-income (odds ratio [OR] 5·8 [95% CI 3·8–8·8]; p<0·0001) and upper-middle-income (1·6 [1·2–2·2]; p=0·0024) country status; age 15–18 years (1·6 [1·1–2·2]; p=0·013); absolute lymphocyte count of 300 or less cells per mm 3 (2·5 [1·8–3·4]; p<0·0001), absolute neutrophil count of 500 or less cells per mm 3 (1·8 [1·3–2·4]; p=0·0001), and intensive treatment (1·8 [1·3–2·3]; p=0·0005). Factors associated with treatment modification included upper-middle-income country status (OR 0·5 [95% CI 0·3–0·7]; p=0·0004), primary diagnosis of other haematological malignancies (0·5 [0·3–0·8]; p=0·0088), the presence of one of more COVID-19 symptoms at the time of presentation (1·8 [1·3–2·4]; p=0·0002), and the presence of one or more comorbidities (1·6 [1·1–2·3]; p=0·020). Interpretation: In this global cohort of children and adolescents with cancer and COVID-19, severe and critical illness occurred in one fifth of patients and deaths occurred in a higher proportion than is reported in the literature in the general paediatric population. Additionally, we found that variables associated with treatment modification were not the same as those associated with greater disease severity. These data could inform clinical practice guidelines and raise awareness globally that children and adolescents with cancer are at high-risk of developing severe COVID-19 illness. Funding: American Lebanese Syrian Associated Charities and the National Cancer Institute.